Pelatihan Fleksibilitas Otot pada Remaja Putri sebagai Upaya Menurunkan Nyeri pada Dysmenorrhea - Andi Mappanganro; Andi Tenri Abeng (Idea Pengabdian Masyarakat, 2021)
Menstruation is a cyclical bleeding that occurs in women during the reproductive stage of their life, menstruation is caused by the periodic shedding of the endometrium, this is a natural process in women during their reproductive years and it occurs when the egg is not fertilized. One of the complaints about menstrual pain is dysmenorrhea which is menstrual pain caused by uterine activity, without any pathological abnormalities from the pelvis. Efforts that can be made to overcome primary dysmenorrhea is one of flexibility exercises, namely muscle stretching. Muscle stretching exercises are simple, safe and effective exercises performed by people with dysmenorrhea to maintain and develop flexibility or flexibility. Flexibility exercises will stretch the muscles in the abdomen and pelvis so that it will increase blood flow to the uterus and relax the uterine muscles. To avoid the adverse effects of decreased flexibility and overcome complaints during menstruation (dysmenorrhea), an effort is needed that can increase awareness of the importance of physical activity and relaxation methods to relieve menstrual pain, namely through training that discusses the importance of physical activity to maintain muscle flexibility and methods stretching to reduce symptoms of dysmenorrhea